STUDI PEMETAAN PETA KOTA (STUDI KASUS KOTA MANADO) - Sendow, Theo Kurniawan; Jefferson, Longdong (Sam Ratulangi University, 2012)
The rapid physical growing of Manado city influenced the city’s structure so that the current city’s map is not accurate because there are new streets that haven’t been pictured in the current city’s map. So an accurate delineation is needed to drumming up the Manado’s physical growing. TheGlobal Positioning System (GPS) is needed to draw an accurate street network map.The Manado’s street network map is a tool to obtain the image of the street network’s scientific data by drawing the signs and informations so that can be easily read and understandable. In the planning to make Manado’s street network map, research with the GPS Garmin 76CSx model is carrying out. GPS is a tool to detect a point at the earth’s surface with enough high carefulness. In a determining a position, the GPS’s receiving units receive the signals from GPS satellite and do the computation about the signals.In this research, to get to draw the Manado’s street network structure two important phases are carrying out which are data collecting process and drawing process with computerization. In the data collecting process, survey with GPS at all the street network in the Manado city’s range iscarrying out. And in the drawing process with computerization using computer soft wares which are MapSource and AutoCAD 2008, all of the data from GPS are transfered to computer which will be processed with the two programs.The street network tracking survey is carrying out so that every coordinate point in the Manado can be specified. The determining of the streets’ internodes is needed to process the coordinate point.The drawing process is carrying out in some phases, started with the GPS calibration to the street network drawing. From the drawing process, we can see that the carefulness of Bakosurtanal map is different with the GPS’s map. At the GPS’s map there are new streets that are none in the Bakosurtanal map and there are also the old streets that are gone now because of the housing development.Keywords: Map, Street Network, GPS